SIKAP TERHADAP PENGGUNAAN ALAT DAN METODE KONTRASEPSI PADA PRIA DI KOTA KUPANG - Hetmina, M. E.; Lerik, M.D. Ch.; Takaeb, Afrona; Retnowati (Pergizi Pangan DPD NTT, 2010)
Male participation in the use of contraceptive tools and the method of contraception are the real form of awareness and responsibility of family planning program implementation and reproduction health. An action someone takes is the first of all started with attitude. Some one’s positive or negative attitude will affect his/her behaviour. Men are hoped to have a positive attitude to the use of contraceptive tools and the method of contraception. The aim of the research is to find out the male attitude toward the use of contraceptive tools and the method of contraception in Kota Kupang. This research is quantitative in nature and of a cross-sectional study of descriptive type. There were 376 males of reproductive age who had been taken as samples. They were taken by the use of the Multi-Stage Random Sampling technique. The sample has been “proportioned” into four district regions of Kota Kupang. The result of the research showed that 295 men (78.5%) had a positive attitude toward the use of a condom, while 276 men (73.4%) had a positive attitude toward the use of vasectomy. Of all the men who have shown a positive attitude, there were 47 (15.9%) using condom.